2016
DOI: 10.1016/j.orcp.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Self-weighing in weight management interventions: A systematic review of literature

Abstract: Background: Self-weighing increases a person's self-awareness of current weight and weight patterns. Increased self-weighing frequency can help an individual prevent weight gain.Literature, however, is limited in describing variability in self-weighing strategies and how the variability is associated with weight management outcomes. Aim: This review analyzed selfweighing in weight management interventions and the effects of self-weighing on weight and other outcomes. Methods: Twenty-two articles from PubMed, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 39 publications
3
66
0
Order By: Relevance
“…These measurements, however, can be time-consuming and require training and proficiency to provide reliable and useful information for personal and clinical use. Self-monitoring of body weight and various biometrics are effective in the promotion of successful weight loss, weight maintenance, and weight regain prevention [8,9,10]. Assessments of body fat during weight loss intervention are important to enable the preservation of lean body mass [11].…”
Section: Introductionmentioning
confidence: 99%
“…These measurements, however, can be time-consuming and require training and proficiency to provide reliable and useful information for personal and clinical use. Self-monitoring of body weight and various biometrics are effective in the promotion of successful weight loss, weight maintenance, and weight regain prevention [8,9,10]. Assessments of body fat during weight loss intervention are important to enable the preservation of lean body mass [11].…”
Section: Introductionmentioning
confidence: 99%
“…Awareness could trigger a self-evaluation response involving the interpretation of one’s condition against a goal or standard; after self-evaluation, a series of responses could be determined through self-adjustment and self-reinforcement [1,6]. Self-monitoring capitalizes on this motivation to achieve glycemic control [8], improve weight management [9], and reduce hospitalization and readmission rates [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Individuals in the SP condition were given a handout of available resources (i.e., individual telephone sessions and self-monitoring feedback via email when requested, lesson materials). During telephone sessions, counselors encouraged daily self-weighing as one of the most effective tools for weight loss (1)(2)(3)(4)(5)(6)(7). Further details on the sample and study procedures are described elsewhere (15).…”
Section: Methodsmentioning
confidence: 99%
“…Frequent self-weighing is an effective tool for weight loss and weight gain prevention (1)(2)(3)(4)(5)(6)(7), and decreases in self-weighing are associated with subsequent weight gain (8). Extensive research refutes the common misperception that self-weighing increases long-term psychological distress and body dissatisfaction (5,9). In fact, some studies have suggested frequent self-weighing increases body satisfaction over time (10,11).…”
Section: Introductionmentioning
confidence: 99%